La musicoterapia como facilitadora de la construcción de identidad de un grupo intergeneracional del centro CREA- Roma de Bogotá: paralelo entre la narrativa verbal y la narrativa musical (2019)
Identity is a dynamic, flexible and constantly changing construct, where what remains is the narrative, the self-narrative that the individual or group makes about who he/she is. The main objective of this project was to describe how music therapy facilitated the construction of an intergenerational group's identity, through an analysis of the musical and verbal narrative of the participants, in favor of healthy living. A 27-session music therapy process was carried out in favor of the construction of Identity in an intergenerational group (average of 24 participants between the ages of 8-38), within the context of the Musical Education sessions of the Hands to the Center line. Believe of Rome, of IDARTES. A qualitative research design was proposed, where various information gathering techniques are used, the quality systematized in a Triangulation Matrix to be integrated with the theory in a Therapeutic Narrative Analysis (Aldridge, 1996, 2005). It is concluded that music therapy encourages the transformation and discovery of new forms of expression through the co-creation of a safe, respectful, horizontal and creative space, where the encounter from the human, emotional, musical, bodily, contributes to the construction of identity, as an individual, as a group, as artists and as Colombians. All of the above in the framework of the realization of the project of work of the Master's Degree in Music Therapy of the National University of Colombia- Bogotá.